Association of periodontal status and metabolic control in periodontitis patients with diabetes mellitus in Hospital Pakar Universiti Sains Malaysia - Assmar, Ainatul Husna; Taib, Haslina; Mohamad, Noraini; Awang Nawi, Mohamad Arif; Wan Mohamad, Wan Majdiah (IIUM Journal of Orofacial and Health Sciences, 2025)
Evidence establishes diabetes mellitus (DM) as a significant risk factor for periodontitis. Periodontitis with DM patients exhibit more pronounced periodontal loss, elevated clinical attachment levels (CAL), and deeper periodontal pockets. This study aims to determine the association between periodontal status and metabolic control indicators in periodontitis with type 2 DM patients. A retrospective record review study was conducted from 2015 to 2024 at Periodontal Clinic, Hospital Pakar Universiti Sains Malaysia. All data of periodontitis with Type 2 DM patients were recorded and analyzed using SPSS 29.0. Demographic data was analysed descriptively and Fisher’s exact test was used to evaluate the association between periodontal status and metabolic control indicators. Fourty two periodontitis patients were included with the mean (SD) age of 59.26 (9.97) years and male predominance (61.9%). Most patients were Malay (97.6%), and 28.6% had blood pressure of more than 140/90 mmHg. Periodontal status revealed 61.9% of patients were in stage 3 and 14.3% in stage 4 with grade B periodontitis was the most common (59.5%). Metabolic control indicators showed 64.3% of patients has HbA1c of ?7.0%, 83.3% has fasting blood glucose of >6.0 mmol/L, and 54.8% with LDL of >2.6 mmol/L. Fisher’s exact test analysis shows no significant association between periodontal severity and metabolic control indicators, including HbA1c (p=0.513), fasting blood glucose (p=0.539), and fasting lipid profiles (p? 0.05). The findings highlight a high prevalence of severe periodontitis among patients with poor glycemic control. However, no significant association of periodontal status and metabolic control indicators.